SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT PADA TANAMAN CABAI MENGGUNAKAN METODE CASE BASED REASONING BERBASIS WEBSITE - Astri Fatkiah; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Chili is a plant that has quite high economic value, chili plants are also widely cultivated by Indonesian farmers. In addition, chili plants also have good nutrition for anti-oxidants. Chili plants are one type of agriculture that is needed in everyday life, because this type of plant has many benefits, besides that chili plants are horticultural plants that are widely used for food needs. There are several problems in the cultivation of chili plants, namely it is difficult to detect or know the symptoms or causes of damage to the chili plants so that the chilies can be damaged such as rot, attacked by pests. The main obstacle to this problem is disease and pest attacks. Diseases and pests can be very detrimental to farmers, causing decreased yields and crop failure. An expert system for diagnosing chili plant diseases based on a website is one way to stimulate the handling of diseases that often occur in this plant. By identifying the symptoms that arise from chili plants with the same level of similarity, this expert system is created or designed using a case-based inference method, this compares the previous case with what happened, and performs the calculation of the Nearest Neighbor Similarity method in determining the expected similarity number of symptoms. solution to the problem above.